Roles of the Survivin BIR Domain in Cellular Apoptosis and Proliferation: An In Silico Study - Nihayah, Silviatun; Wanandi, Septelia Inawati; Erlina, Linda; Syahrani, Resda Akhra (Makara Journal of Science, 2025)
Survivin is an antiapoptotic protein that is highly expressed in cancer cells. We investigated the dual roles of the Bacu-lovirus IAP Repeats (BIR) domain within survivin, encompassing both apoptosis and proliferation, through an in silico study. The protein-protein interaction (PPI) network of survivin was analyzed using Cytoscape software. Functional enrichment (FE) analysis and data from the Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to identify the implicated signaling pathways. The binding affinity of the BIR domain with the targeted proteins was visualized via molecular docking analysis. Drawing insights from the PPI network and FE analysis, we identified two key proteins in-volved in apoptosis such as X-linked Inhibitor of Apoptosis Proteins (XIAP) and caspase-9, and proliferation such as Cyclin-dependent Kinase 1 (CDK1) and Inner Centromere Protein (INCENP) for further analysis of their binding with the survivin BIR domain. These proteins were found to bind to the BIR domain at the Thr34, Thr48, and Ser20 resi-dues that have critical roles to regulate the apoptosis and proliferation. This study provides future insights into how the BIR domain of survivin could emerge as a potential target for cancer treatment, such as determining knockout targets for the development of genome editing technology